Seismic performance evaluation of crumb rubber concrete frame structure using shake table test. (April 2021) - Khan, Izzat; Shahzada, Khan; Bibi, Tayyaba; Ahmed, Asfandyar; Ullah, Hanif
Abstract: The research work presented in this paper has been carried out to investigate the dynamic characteristics and seismic performance parameters of reinforced concrete frame structure built in crumb rubber. Two test specimens were fabricated in reduced scale 1:3 and tested under seismic loading using the shake table. One of the test models was made of normal reinforced concrete, which was used as a reference. The second model was fabricated of reinforced concrete having rubber crumb; replacing the volume of fine aggregates partially by crumb rubber particles. The test specimens were subjected to free vibration test followed by dynamic testing having multiple base excitations using Northridge 1994 accelerogram to explore the dynamic characteristics and seismic response parameters, respectively. The results demonstrated that the partial inclusion of rubber crumb in concrete reduces compressive strength, density, and yield strength. Fundamental period of vibration and damping ratio were increased for crumb in concrete frame. Damage pattern of both the frames was observed and recorded. These results suggested that fine aggregates in concrete can be confidently replaced partially by crumb rubber particles in structures subjected to seismic loadings.